2023
DOI: 10.3390/cancers15102738
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hypoxia-Inducible Factor-1α for the Management of Hepatocellular Carcinoma

Abstract: Hypoxia-inducible factor 1 alpha (HIF-1α) is a transcription factor that regulates the cellular response to hypoxia and is upregulated in all types of solid tumor, leading to tumor angiogenesis, growth, and resistance to therapy. Hepatocellular carcinoma (HCC) is a highly vascular tumor, as well as a hypoxic tumor, due to the liver being a relatively hypoxic environment compared to other organs. Trans-arterial chemoembolization (TACE) and trans-arterial embolization (TAE) are locoregional therapies that are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Cellular signaling pathways involving HIF-1α have been identified as universal biosensors and regulators in a variety of living cells under various hypoxic conditions ( Carmeliet et al, 1998 ). It has been indicated that HIF-1a regulates the cellular response to hypoxia and leads to excessive angiogenesis ( Huynh et al, 2023 ). And when hypoxia occurs, the catabolism of HIF-1α decreases, while its synthesis rate remains unchanged or increases through transcriptional or translational regulatory pathways, the concentration of HIF-1α increases rapidly, and the success of hypoxia modeling can be judged by whether the expression of HIF-1α is elevated ( Fallah and Rini, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular signaling pathways involving HIF-1α have been identified as universal biosensors and regulators in a variety of living cells under various hypoxic conditions ( Carmeliet et al, 1998 ). It has been indicated that HIF-1a regulates the cellular response to hypoxia and leads to excessive angiogenesis ( Huynh et al, 2023 ). And when hypoxia occurs, the catabolism of HIF-1α decreases, while its synthesis rate remains unchanged or increases through transcriptional or translational regulatory pathways, the concentration of HIF-1α increases rapidly, and the success of hypoxia modeling can be judged by whether the expression of HIF-1α is elevated ( Fallah and Rini, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of PD-L1 mediated by the hypoxia-inducible factor (HIF) pathway is an important strategy to enhance cancer immune responses. For example, inhibition of HIF-1α synthesis suppresses PD-L1 expression and induces lysosomal degradation of PD-L1, thereby enhancing the ability of CTL to kill cancer cells ( Huynh et al, 2023 ). In addition, regulating iron metabolism, activating autophagy, or activating nitric oxide synthase 2 (NOS2), thereby promoting TAM metabolic reprogramming towards glycolysis and arginine catabolism, are effective strategies for targeting TAMs for malignancies ( Jayaprakash et al, 2018 ; Muliaditan et al, 2018 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…The targeting of HIFs has been recognized as a prospective strategy for enhancing cancer therapies [ 8 , 9 , 10 ]. A number of small molecular inhibitors targeting HIF have been developed and incorporated into various drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%